IMPLEMENTASI METODE INTERPOLASI LINEAR UNTUK PEMBESARAN RESOLUSI CITRA - Kristoko Dwi Hartomo (Faculty of Industrial Technology Universitas Islam Indonesia, 2006)
Processing an image is a process and image analysis which entangling many visual perceptions and in course have some characteristics of input data and output information in binding digital image. Process of changing measure for an image through magnification of resolution or measure often needed to showing the detail, for demonstration at a physic appliance, and for making of document. At the process on enlarging image resolution, method that would be used in this paper is linear interpolation. Linear Interpolation Method is mathematics algorithm which could be applied to appraise the middle price point through a diametrical line, two successive input point. The system in this paper could process image with algorithm of linear interpolation and become a new photo image with image resolution of pixel larger than the original image.Keywords: image, resolution, linear, interpolation, pixel